2018
DOI: 10.1039/c7en00974g
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of broth chemistry on silver ion release, surface chemistry composition, and bacterial cytotoxicity of silver nanoparticles

Abstract: We determine the impact of bacterial growth media on silver nanoparticle surface chemistry, this surface chemistry on silver ion release from the nanoparticles, and ultimately the antimicrobial implications of those parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 45 publications
1
37
0
Order By: Relevance
“…Pseudospherical citrate-capped AgNPs were synthesized according to a previously reported procedure [20][21][22] and functionalized with poly(ethylene glycol) methyl ether thiol (PEGSH, average molecular weight 1,000 g mol −1 ) using mass action ligand exchange (Scheme S1 in ref. 20 ).…”
Section: E Coli Develops Resistance To Agnps But Not To Ag(i) Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudospherical citrate-capped AgNPs were synthesized according to a previously reported procedure [20][21][22] and functionalized with poly(ethylene glycol) methyl ether thiol (PEGSH, average molecular weight 1,000 g mol −1 ) using mass action ligand exchange (Scheme S1 in ref. 20 ).…”
Section: E Coli Develops Resistance To Agnps But Not To Ag(i) Ionsmentioning
confidence: 99%
“…Pseudospherical citrate-capped AgNPs were synthesized according to a previously reported procedure [20][21][22] and functionalized with poly(ethylene glycol) methyl ether thiol (PEGSH, average molecular weight 1,000 g mol −1 ) using mass action ligand exchange (Scheme S1 in ref. 20 ). Poly(ethylene glycol) methyl ether thiol is a widely used biocompatible and charge-neutral ligand 20,23 which mitigates electrostatic attractive forces with negatively charged bacteria.…”
Section: E Coli Develops Resistance To Agnps But Not To Ag(i) Ionsmentioning
confidence: 99%
“…5). As a background, antibacterial tests with AgNPs and silver-releasing materials have previously been performed in different bacterial culture media 50,51 , phosphate buffer 3,16 , PBS buffer 18,33 , simple aquatic media (for example containing only NaCl and KCl 52 ), dechlorinated tap water 53 or deionized water 32 . However, in these cases, [Cl − ] is typically either very high or very low compared to freshwaters.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have reported that bacterial growth media could impact on ions bioavailability and therefore on cell's response and shape under stress condition [41][42][43] . We can suspect that, since culture media contains different chemical compounds as phosphates and chlorates, silver precipitation may occur distinctly depending on the medium composition.…”
Section: Effect Of Culture Media (Malate Medium Versus Lb Medium) On Ag + Toxicity In R Gelatinosusmentioning
confidence: 99%
“…More details analysis, trying to distinguish between several chemical compounds (phosphates, malic acid, carboxylates, chlorates, …) in broth composition 42,43,53,54 and also light effect, is actually carried in our group. Furthermore, these preliminary results are sufficient to establish a link between observed aggregates and silver precipitation process due to medium solution.…”
Section: Formation Of Ag + Aggregates In Malate/lb or Citratementioning
confidence: 99%